2011
DOI: 10.1177/1359105311414955
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Sunscreen Use in Women by a Theory-Based Online Intervention: A Randomized Controlled Trial

Abstract: This study compares a motivational skin cancer prevention approach with a volitional planning and self-efficacy intervention to enhance regular sunscreen use. A randomized controlled trial (RCT) was conducted with 205 women (mean age 25 years) in three groups: motivational; volitional; and control. Sunscreen use, action planning, coping planning and coping self-efficacy were assessed at three points in time. The volitional intervention improved sunscreen use. Coping planning emerged as the only mediator betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…The personal values and beliefs of patients have been suggested to be barriers to such prevention (specifically the use of sunscreens) 8 . For example, a tendency toward tanning or misconceptions about skin cancer risk factors are correlated with lower use of sunscreens 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The personal values and beliefs of patients have been suggested to be barriers to such prevention (specifically the use of sunscreens) 8 . For example, a tendency toward tanning or misconceptions about skin cancer risk factors are correlated with lower use of sunscreens 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data in the setting of primary prevention demonstrate that sun protection is closely correlated with a patient's level of self-motivation to engage in their own care [10][11][12] . In the present study, we used sunprotective behaviors as a proxy to evaluate personal willingness to participate in tertiary prevention 8 . We examined four different preventive strategies and observed that each was suboptimally used by cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this association, various recent experimental studies to test these effects in young target groups aimed at promoting sunscreen use as an end point [19][20][21][22], and others used various UV protection behaviors (including avoiding sunbeds) or behavior scores [23][24][25][26][27][28][29][30][31][32][33][34]. Given the substantial amount of time that children and adolescents of all social backgrounds spend in the school environment, addressing skin cancer prevention in this setting is crucial and provides a unique opportunity to propel skin cancer prevention programs [35].…”
Section: Introductionmentioning
confidence: 90%
“…As noted by the Task Force, research to test a multilevel approach to improve adoption of sun protection has seldom been attempted. We reviewed an additional 17 randomized controlled trials that tested interventions to change sun protection behavior in adults, published and available on PubMed since that systematic review (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). From these, we identified only 2 that appeared to purposefully take a multilevel approach to intervention design and testing, with promising results (54,60).…”
Section: The Need For a Comprehensive Approach To Skin Cancer Preventionmentioning
confidence: 99%